Abnormal cell sorting and altered early neurogenesis in a human cortical organoid model of Protocadherin-19 clustering epilepsy - Niu, Wei; Deng, Lu; Mojica-Perez, Sandra P.; Tidball, Andrew M.; Sudyk, Roksolana; Stokes, Kyle; Parent, Jack M. (Frontiers in Cellular Neuroscience, 2024)
Protocadherin-19 (PCDH19)-Clustering Epilepsy (PCE) is a developmental and epileptic encephalopathy caused by loss-of-function variants of the PCDH19 gene on the X-chromosome. PCE affects females and mosaic males while male carriers are largely spared. Mosaic expression of the cell adhesion molecule PCDH19 due to random X-chromosome inactivation is thought to impair cell-cell interactions between mutant and wild type PCDH19-expressing cells to produce the disease.Progress has been made in understanding PCE using rodent models or patient induced pluripotent stem cells (iPSCs). However, rodents do not faithfully model key aspects of human brain development, and patient iPSC models are limited by issues with random X-chromosome inactivation. To overcome these challenges and model mosaic PCDH19 expression in vitro, we generated isogenic female human embryonic stem cells with either HA-FLAG-tagged PCDH19 (WT) or homozygous PCDH19 knockout (KO) using genome editing. We then mixed GFP-labeled WT and RFP-labeled KO cells and generated human cortical organoids (hCOs). We found that PCDH19 is highly expressed in early (days 20-35) WT neural rosettes where it co-localizes with N-Cadherin in ventricular zone (VZ)-like regions. Mosaic PCE hCOs displayed abnormal cell sorting in the VZ with KO and WT cells completely segregated. This segregation remained robust when WT:KO cells were mixed at 2:1 or 1:2 ratios. PCE hCOs also exhibited altered expression of PCDH19 (in WT cells) and N-Cadherin, and abnormal deep layer neurogenesis. None of these abnormalities were observed in hCOs generated by mixing only WT or only KO (modeling male carrier) cells. Our results using the mosaic PCE hCO model suggest that PCDH19 plays a critical role in human VZ radial glial organization and early cortical development. This model should offer a key platform for exploring mechanisms underlying PCE-related cortical hyperexcitability and testing of potential precision therapies.